Characterization of Fine and Coarse Atmospheric Aerosols in Kuala Lumpur - Mohd Yusoff, Mohd Rashid; Rahmalan, Ahamad; Wood, Abdul Khalik (Universiti Putra Malaysia Press, 1997)
From July 1988 to December 1990 daily samples of atmospheric aerosols segregated into fine particlas, FP (aerodynamic diameter, da 2.5 !Lm) and coarse particles, CP (2.5!Lm ~ da ~ 10 !Lm) were collected using a dichotomous sampler sited at the Universiti Teknologi Malaysia, Kuala Lumpur. Eighteen elements (AJ, As, Br, Ca, Cl, Co, Fe, K, Mn, Na, i, P, Pb, S, Sb, Si, V, and Zn) were determined from the aerosol samples. On average, the total elemental concentration made up 19, 33, and 23% of the FP, CP, and TP (TP=FP+CP) fractions respectively, and approximately 70% of As, Br, K, Na, Pb, S, and V were found to be in the fine fraction. Both Sand Si constituted the largest percentage of the total elemental concentration of 61 and 44% in the FP and CP fractions, respectively. Based on a source apportionment study, the soil and marine environments contributed 21 and 5% of the TP fraction while the remaining 74% of the aerosol concentration is yet to be explained.